2018
DOI: 10.1186/s13063-018-2468-z
|View full text |Cite
|
Sign up to set email alerts
|

Text4Heart II – improving medication adherence in people with heart disease: a study protocol for a randomized controlled trial

Abstract: BackgroundCardiac rehabilitation (CR) is an essential component of contemporary management for patients with coronary heart disease, including following an acute coronary syndrome (ACS). CR typically involves education and support to assist people following an ACS to make lifestyle changes and prevent subsequent events. Despite its benefits, uptake and participation in tradition CR programs is low. The use of mobile technologies (mHealth) offers the potential to improve reach, access, and delivery of CR suppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 56 publications
0
23
1
Order By: Relevance
“…Due to the absence of similar work, a comparison of these findings with previous research is not possible. Nevertheless, this pattern of influence did not support previous work where sending health information via text messages did not only improve the knowledge, skills, compliance, adherence and attitudes among individuals but also with their selfefficacy (19,(26)(27)(28)(29)(30)(31)(32). Again, it could be possible that factors like the SMS timing, frequency, content of the text message and even the number of text messages could have affected the outcomes of this study.…”
Section: Discussioncontrasting
confidence: 80%
See 3 more Smart Citations
“…Due to the absence of similar work, a comparison of these findings with previous research is not possible. Nevertheless, this pattern of influence did not support previous work where sending health information via text messages did not only improve the knowledge, skills, compliance, adherence and attitudes among individuals but also with their selfefficacy (19,(26)(27)(28)(29)(30)(31)(32). Again, it could be possible that factors like the SMS timing, frequency, content of the text message and even the number of text messages could have affected the outcomes of this study.…”
Section: Discussioncontrasting
confidence: 80%
“…International studies have demonstrated that mobile text messaging can be an effective tool to enhance an individual's knowledge on disease, disease prevention and management, health screening methods, and healthpromoting and preventive behaviours (16,(26)(27)(29)(30)(31)(32)35). This study found that breast CA and BSE knowledge among women can be enhanced through the use of mobile text messaging.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…With the advancement of technology, electronic reminder system (pager, telephone, and audio-visual devices) are being used to proactively deliver reminders. Behaviour of patients can be influenced by mobile phones due to its ease of use, worldwide acceptance and instant information transmitting capabilities (Maddison et al, 2018). These systems if united with alternate behavioural strategies could solve the problems of non-adherence largely.…”
Section: Active Remindersmentioning
confidence: 99%